The 2003 California recall election : an analysis of news framing and the celebrity. - Seah, Lucinda Kar Hui. (2008)
This dissertation examined how celebrity candidates were framed in political discourse, specifically in election news coverage. It proposed that the news frames on celebrity candidates would revolve around their public persona(s) and star power more so than their credibility as a politician.